Too hard to get - Oguntoye, Jide (Rasmed Publications Ltd, 2004)
Kola Abere got married to Felicia and she was made to believe that peju Ojo is Kola's relation. Hitherto, Peju was regarded as a sister-in-law by Felicia. Felicia got transferred out of her base to another town and this gave Kola and Peju the chance to continue with their illicit affairs.
Keywords: Drama